SYSTEMATIC REVIEW (SLR) ON THE IMPACT OF INDUSTRIAL CLASSES ON THE JOB READINESS OF VOCATIONAL HIGH SCHOOL GRADUATES - Maulana Sulton; Yoto Yoto; Didik Nurhadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to deeply analyze the role of the implementation of industrial class programs in Vocational High Schools in improving hard skills, soft skills, and graduates' work readiness through a Systematic Literature Review (SLR) approach. The study was conducted using the PRISMA framework and utilized the Publish or Perish database to select relevant articles. A rigorous selection process resulted in eight primary Indonesian-language articles that met the inclusion criteria for comprehensive analysis. The study results indicate that research on industrial classes remains relatively limited, with a significant increase in publications only occurring after 2022. The effectiveness of this program is influenced by several important factors, such as close partnerships between schools and industry, curriculum alignment with workplace standards, educator competency, facility availability, and ongoing training and internships. However, challenges such as limited resources, curriculum synchronization, and suboptimal industry commitment remain major obstacles to its implementation. Overall, the findings of this study confirm that industrial classes play a strategic role in developing students' technical and non-technical skills, while also serving as a bridge between education and the workplace. This program has significant potential to strengthen the competencies and increase the competitiveness of vocational high school graduates in the modern industrial era.